2020
DOI: 10.1177/1403494820953325
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in attitudes towards a school-based smoking prevention intervention

Abstract: Aims: There are well-known gender differences in smoking, including the pattern of use and the effectiveness of smoking prevention programs. However, little is known about the differences between boys and girls in their attitudes towards smoking prevention interventions. This study explores gender differences in attitudes towards a school-based intervention to prevent smoking. Methods: We used data from the X:IT II intervention study conducted in 46 Danish elementary schools. Results: Compared to boys, girls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
(25 reference statements)
2
9
0
Order By: Relevance
“…More girls than boys reported in this study that regulations about smoking (i.e., not being allowed to smoke by parents and not being allowed to smoke before the age of 18) were important reasons for not smoking. These findings are in line with existing research indicating that girls and young females have more positive attitudes towards smoking regulations-both at the societal and school level as well as at home [8,16].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More girls than boys reported in this study that regulations about smoking (i.e., not being allowed to smoke by parents and not being allowed to smoke before the age of 18) were important reasons for not smoking. These findings are in line with existing research indicating that girls and young females have more positive attitudes towards smoking regulations-both at the societal and school level as well as at home [8,16].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, research shows that boys are more attracted to smoking cigarettes compared with girls [6,7]. In a recent study, we found that girls have more positive attitudes towards several elements of smoking prevention initiatives (e.g., rules for smoking at school) [8]. Hence, gender differences exist in both smoking uptake and in the adoption of smoking preventive initiatives.…”
Section: Introductionmentioning
confidence: 88%
“…More girls than boys reported in this study that regulations about smoking (i.e., not being allowed to smoke by parents and not being allowed to smoke before the age of 18) were important reasons for not smoking. These ndings are in line with existing research indicating that girls and young females have more positive attitudes towards smoking regulations -both at the societal and school level as well as at home (8,16).…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study, we found that girls have more positive attitudes towards several elements of smoking prevention initiatives (e.g., rules for smoking at school) (8). Hence, gender differences exist in both smoking uptake and in the adoption of smoking preventive initiatives.…”
Section: Introductionmentioning
confidence: 85%
“…In addition, neither of the studies address the adolescents' attitudes toward the concept of signing a contract. In a previously study we addressed gender differences in relation to aspects of the SFA and the results showed that boys and girls seem to relate differently to the SFA which is suggested to re ect that girls, in general, are more positive towards parental involvement then boys (26). This indicates that the SFA appeal differently to adolescents with different characteristics.…”
Section: Introductionmentioning
confidence: 97%